A Framework Module Of Holistic Human Development In Facing Of Global Economic Transformation - Abd Jalil, Borham (2013)
This paper propose a framework module of holistic human development, which are facing global economic transformation. It is related to the concept of human development where they need to be developed and nurtured in a holistic manner from both physical and spiritual aspects in accordance with the nature of creation to create a life that is pleasing to the Creator. Human today are in pursuit to get to the peak of development based on science and technology to face global economic transformation. Through the development of science and technology, they are fully exploiting the bounty of natural resources and facilities for the comfort of God in their lives. However, one fact that is hard to deny the nature and pattern of development carried out by human today have caused so much crises or problems either to the community or physical environment. Transformed by today’s human evolution; marked by the increased crime rates, the collapse of the family institution, increased symptoms of moral decay in society, the emergence of unethical younger generation, damages to the environment and other social problems are getting chronic. Looking at the social and cultural development, it is important to have an assessment and review the model of development and education. Paradigm or archetype for the development of a society will determine the type and pattern of development and education that will be carried out within the community. The concept of development and education based on basic and incomprehensive views will not produce any better result from what we have now.